2022
DOI: 10.3389/fendo.2022.1011669
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin mitigates ferroptosis and improves myocardial oxidative stress in mice with diabetic cardiomyopathy

Abstract: Canagliflozin (Cana), an anti-diabetes drug belongs to sodium-glucose cotransporter 2 inhibitor, is gaining interest because of its extra cardiovascular benefits. Ferroptosis is a new mode of cell death, which can promote the occurrence of diabetic cardiomyopathy (DCM). Whether Cana can alleviate DCM by inhibiting ferroptosis is the focus of this study. Here, we induced DCM models in diabetic C57BL6 mice and treated with Cana. Meanwhile, in order to exclude its hypoglycemic effect, the high glucose model in H9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…Another example includes a study in which the effects of Canagliflozin (Cana) on ferroptosis in mice with DCM were examined. In this report, Cana reduced inflammatory cell infiltration into myocardial fibers and rescued the excess iron accumulation and glutathione depletion seen in ferroptosis (Du et al, 2022). As mentioned previously, ferroptosis is iron-induced cell death involving a loss of GPx4 activity and a subsequent increase in lipid reactive oxygen species, resulting in lipid peroxidation (Yang and Stockwell, 2016).…”
Section: Connections Between Inflammation and Iron Metabolism In Card...supporting
confidence: 74%
“…Another example includes a study in which the effects of Canagliflozin (Cana) on ferroptosis in mice with DCM were examined. In this report, Cana reduced inflammatory cell infiltration into myocardial fibers and rescued the excess iron accumulation and glutathione depletion seen in ferroptosis (Du et al, 2022). As mentioned previously, ferroptosis is iron-induced cell death involving a loss of GPx4 activity and a subsequent increase in lipid reactive oxygen species, resulting in lipid peroxidation (Yang and Stockwell, 2016).…”
Section: Connections Between Inflammation and Iron Metabolism In Card...supporting
confidence: 74%
“…Due to the limited regenerative capacity of the myocardium in mammalian adult hearts, inhibition of cardiomyocyte death might be one of the important ways to alleviate DCM [103]. In our studies, we induced DCM models in diabetic C57BL6 mice and treated with canagliflozin and found that canagliflozin mitigates ferroptosis and improves myocardial oxidative stress in mice with diabetic cardiomyopathy [104]. Taken together, taking ferroptosis as the starting point may provide a new strategy for the prevention and control of DCM.…”
Section: Ferroptosis and Diabetic Cardiomyopathymentioning
confidence: 74%
“…At the cellular level, the pathways of iron, amino acids and lipid metabolism are involved in the initiation and execution of ferroptosis (Du et al, 2022). As Figure 7 shown, iron, transported into cells by TfR1, is either stored in ferritin or exported by FPN1.…”
Section: Discussionmentioning
confidence: 99%
“…RNA was extracted and quantified according to the previous operation methods of our research group (Du et al, 2022). Total…”
Section: Rna Extraction and Quantitative Pcr (Qpcr)mentioning
confidence: 99%